2021
DOI: 10.3390/nu13082631
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition and Oxidant Load in Neonates

Abstract: Neonates with preterm, gastrointestinal dysfunction and very low birth weights are often intolerant to oral feeding. In such infants, the provision of nutrients via parenteral nutrition (PN) becomes necessary for short-term survival, as well as long-term health. However, the elemental nutrients in PN can be a major source of oxidants due to interactions between nutrients, imbalances of anti- and pro-oxidants, and environmental conditions. Moreover, neonates fed PN are at greater risk of oxidative stress, not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 154 publications
(201 reference statements)
0
13
0
1
Order By: Relevance
“…Parenteral nutrition in newborns and infants can prove to be a major source of oxidants [50]; several studies have suggested that higher arginine and cysteine intake, along with decreased iron and copper concentrations, might help decrease the oxidant load. The range of products used for parenteral nutrition must be strictly controlled in terms of storage conditions and period, exposure to the sun and oxygen, and the temperature of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral nutrition in newborns and infants can prove to be a major source of oxidants [50]; several studies have suggested that higher arginine and cysteine intake, along with decreased iron and copper concentrations, might help decrease the oxidant load. The range of products used for parenteral nutrition must be strictly controlled in terms of storage conditions and period, exposure to the sun and oxygen, and the temperature of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous risk factors for PNAC have led to various hypotheses to explain its pathogenesis. It is now believed that biologically active factors absorbed from the injured and hyperpermeable intestine, combined with components of PN solutions ( 19 ), synergize to cause hepatic inflammation, cholestasis, and subsequent fibrosis ( 7 ). Clinicopathological features of PNAC include cholestasis, variable portal vein inflammation, steatosis, and, ultimately, fibrosis and cirrhosis ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this recommendation should also be extended to PN for adults, since components used for adults are also susceptible to photo-oxidation. Moreover, the use of multilayered bags is also recommended to prevent oxidation [ 37 , 39 , 43 ].…”
Section: Vascular Access and Administrationmentioning
confidence: 99%
“…With regard to the stability of the admixture, some nutrients have a destabilizing effect in the presence of other nutrients. Similarly, there are general factors affecting PN admixture stability [ 6 , 35 , 37 , 38 , 39 , 43 , 45 , 55 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]: Temperature: For example, with increased temperature, there is a raised likelihood of calcium-phosphate precipitate formation and of the degradation of several amino acids. pH: The optimal pH for IVFE stability is in the range of 6–9, whereas calcium phosphate solubility is better at lower pH values.…”
Section: Composition Of Pn Admixturesmentioning
confidence: 99%